Lymphoproliferative disorder in pleural effusion in a subject with past asbestos exposure. (2015) - Hara, Naofumi; Fujimoto, Nobukazu; Miyamoto, Yosuke; Yamagishi, Tomoko; Asano, Michiko; Fuchimoto, Yasuko; Wada, Sae; Ozaki, Shinji; Kishimoto, Takumi
Abstract: Primary effusion lymphoma (PEL) is a subtype of non-Hodgkin lymphoma that presents as serous effusions without detectable masses or organomegaly. Here we report a case of PEL-like lymphoma in a patient with past asbestos exposure. A 65-year-old man was referred to our hospital due to dyspnea upon exertion. He had been exposed to asbestos for three years in the construction industry. Chest X-ray and CT images demonstrated left pleural effusion. Cytological analysis of the pleural effusion revealed large atypical lymphocytes with distinct nuclear bodies and high nucleus-to-cytoplasm ratio. Immunohistochemical analyses showed that the cells were CD20 +, CD3 −, CD5 −, and CD10 − . These findings led to a diagnosis of diffuse large B-cell lymphoma. PEL or PEL-like lymphoma should be considered a potential cause of pleural effusion in subjects with past asbestos exposure.